Association between birth weight and childhood cardiovascular disease risk factors in West Virginia. (15th August 2019) - Umer, Amna; Hamilton, Candice; Cottrell, Lesley; Giacobbi, Peter; Innes, Kim; Kelley, George A.; Neal, William; John, Collin; Lilly, Christa
Abstract: The reported associations between birth weight and childhood cardiovascular disease (CVD) risk factors have been inconsistent. In this study, we investigated the relationship between birth weight and CVD risk factors at 11 years of age. This study used longitudinally linked data from three cross-sectional datasets ( N = 22, 136) in West Virginia; analysis was restricted to children born full-term ( N = 19, 583). The outcome variables included resting blood pressure [systolic blood pressure (SBP), diastolic blood pressure (DBP)] and lipid profile [total cholesterol (TC), low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, non-HDL, and triglycerides (TG)]. Multiple regression analyses were performed, adjusting for child's body mass index (BMI), sociodemographics, and lifestyle characteristics. Unadjusted analyses showed a statistically significant association between birth weight and SBP, DBP, HDL, and TG. When adjusted for the child's BMI, the association between birth weight and HDL [ b = 0.14 (95% CI: 0.11, 0.18) mg/dl per 1000 g increase] and between birth weight and TG [ b = –0.007 (–0.008, –0.005) mg/dl per 1000 g increase] remained statistically significant. In the fully adjusted model, low birth weight was associated with higher LDL, non-HDL, and TGs, and lower HDL levels. The child's current BMI at 11 years of age partially (for HDL, non-HDL, and TG) and fully mediated (for SBP and DBP) the relationship between birth weight and select CVD risk factors. While effects were modest, these risk factors may persist and amplify with age, leading to potentially unfavorable consequences in later adulthood.